"A Collusive Suit to ""Confound the Rights of Property Through the Length and Breadth of the Colony""?: Busby v White (1859) " - Fletcher, Ned; Elias, Dame Sian (Victoria University of Wellington Law Review, 2010)
In Busby v White, James Busby sought to challenge the validity of the Land Claims Ordinance 1841 which treated his pre-Treaty of Waitangi land purchases as "null and void". He had campaigned against the New South Wales statute which preceded the Ordinance, and throughout the 1840s continued to argue against the legislation through political channels, while maintaining his claim to hold the lands under his "native title". By the 1850s holding by "native title" was increasingly precarious as the Government moved to acquire Busby's lands for the purposes of settlement. Busby was forced to law. His aim was to set up the validity of the legislation as a question of law which could be taken to the Privy Council for authoritative resolution. Busby v White was the second attempt to establish a platform for appeal. As in his earlier claim, Busby v McKenzie, the Supreme Court avoided a determination on the merits, thus thwarting Busby's strategy of appealing to London. Although no substantive decision was delivered, the extensive argument was fully reported in The Southern Cross newspaper, from which the Lost Cases Project has recovered it. Its interest today is in arguments which question the course set by R v Symonds (1847) on the nature of native property in New Zealand and the subsequent relegation of the Treaty of Waitangi to legal limbo in Wi Parata v Bishop of Wellington (1877).